Study of Four Unit System for the Measures of Reliability, Availability & MTSF - Dr. Reena Garg (International Journal of Advanced Science and Technology, 2020)
The paper deals with, availability and profit measures of four unit system using Semi Markov process and Regenerative Point Graphical Technique (RPGT).system has four independent units. System parameters Such as availability, MTSF (Mean Time to System Failure), busy period of repairman, expected no. of repairman visit are evaluated and the variations between these parameters studied by analysing the graphical plotting.